Multi-tissue transcriptome-wide association study identifies novel candidate genes and pleiotropy effects across four abdominal hernia subtypes - Dima L. Chaar; Chen Jiang; Brandon Cowan; Sahil Patel; Mark Kvale; Jie Yin; Rouzbeh Mostaedi; Nadav Ahituv; Eric Jorgenson; Thomas J. Hoffmann; Hélène Choquet (HGG Advances)
Summary: Abdominal hernias are caused by the protrusion of an organ or tissue through a weakened abdominal wall. Genome-wide association studies (GWASs) have identified 81 genetic susceptibility loci for different hernia subtypes, with 26 loci associated with more than one hernia type; however, additional work is needed to prioritize causal genes at known GWAS loci, identify novel ones, and characterize shared genetic effects across hernia subtypes. We conduct transcriptome-wide association study (TWAS) analyses of four hernia subtypes (i.e., inguinal, umbilical, ventral, femoral) using GWAS summary statistics from up to 57,291 hernia cases and 436,717 controls of European ancestry. Our TWAS, which leveraged imputed gene expression from 54 tissues, identifies 211 unique genes, of which 85 did not overlap with known hernia-associated loci. We also investigate patterns of pleiotropy and identify four genes (LYPLAL1-AS1, RIMKLBP2, AL513283.1, and EFEMP1) associated with all four hernia subtypes. Our findings enhance understanding of transcriptomic mechanisms through which hernias develop.